Answer:
x = -10
Step-by-step explanation:
2(x+3) = x-4 --> multiply (x+2) times 2
2x+6 = x - 4 --> subtract x from both sides
x+6 = -4 --> subtract 6 from both sides
x = -10
Answer:
y + 7 =
(x + 6)
Step-by-step explanation:
The equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b ) a point on the line
Here m =
and (a, b ) = (- 6, - 7 ) , then
y - (- 7) =
(x - (- 6) ) , that is
y + 7 =
(x + 6)
Just by comparing the plots of f(x) and g(x), it's clear that g(x) is just some positive scalar multiple of f(x), so that for some constant k, we have
g(x) = k • f(x) = kx² = (√k x)²
The plot of the transformed function g(x) = (√k x)² passes through the point (1, 4), which means
g(1) = (√k • 1)² = 4
and it follows that k = 4. So g(x) = 4x² = (2x)² and B is the correct choice.
Answer:
the answer is 6
Step-by-step explanation:
3×2-0×2=6